The break came: analyzing the divorces of same-sex marriages in Spain - Becerril, Diego (2022)
Law 13/2005 meant the recognition of gay marriage after decades of waiting and attempts to regulate these couples by different Autonomous Communities. This fact made Spain one of the pioneer countries in recognizing this type of marriage. This article addresses the evolution of the dissolution of same-sex marriages as the degree of conflict between them. To do this, quantitative methodology is used through the secondary data review technique, using both the Natural Population Movement (NPM) and the Nullity, Separation and Divorce Statistics (INE). The main conclusions, it is necessary to highlight the gradual and uninterrupted rise in the dissolution of same-sex marriages until 2014. As of this date, the data show greater variability. On the other hand, it is significant that the breakups have a high degree of consensus, the duration of the bonds has been increasing and the presence of children in divorce